Study Protocol on Defining Core Outcomes and Data Elements in Chronic Subdural Haematoma. Issue 4 (28th July 2021) - Holl, Dana C; Chari, Aswin; Iorio-Morin, Christian; Dammers, Ruben; van der Gaag, Niels A; Kolias, Angelos G; Hutchinson, Peter J; Edlmann, Ellie
Abstract: BACKGROUND: Core Outcome Sets (COSs) are necessary to standardize reporting in research studies. This is urgently required in the field of chronic subdural hematoma (CSDH), one of the most common disease entities managed in neurosurgery and the topic of several recent trials. To complement the development of a COS, a standardized definition and baseline Data Elements (DEs) to be collected in CSDH patients, would further improve study quality and comparability in this heterogeneous population. OBJECTIVE: To, first, define a standardized COS for reporting in all future CSDH studies; and, second, to identify a unified CSDH Definition and set of DEs for reporting in future CSDH studies. METHODS: The overall study design includes a Delphi survey process among 150 respondents from 2 main stakeholder groups: healthcare professionals or researchers (HCPRs) and Patients or carers. HCPR, patients and carers will all be invited to complete the survey on the COS, only the HCPR survey will include questions on definition and DE. EXPECTED OUTCOMES: It is expected that the COS, definition, and DE will be developed through this Delphi survey and that these can be applied in future CSDH studies. This is necessary to help align future research studies on CSDH and to understand the effects of different treatments on patient function and recovery. DISCUSSION: This Delphi survey should result in consensus on a COS and a standardized CSDH Definition and DEs to be used in future CSDH studies.